INFLUENCE OF GRAM-NEGATIVE STRAIN KLEBSIELLA OXYTOCA ON BIOCORROSION - S, Chitra; B, Anand (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Several studies of biofilms must accept that biofilms may develop in an enormous number of environments. This biofilm forms colonization on the solid surfaces by extracellular polysaccharides (EPSs) secreted by the microbial cells. The EPSs secreted by microbial cell stimulate corrosion in the engineered materials due to the presence of polyanionic neutral macromolecules. Many techniques have been described measuring and inhibiting microbiologically influenced corrosion; however, none has been accepted as an industry standard. This is because the risks posed to the marine biosphere due to the use of antifouling inhibitors. Recently, a large amount of literature has been edited on the influence of toxic biocides on non-targeted organisms in the marine environment are most likely. It has been shown that the modifications of antifouling inhibitors by the non-toxic drugs can reduce microbial adhesion and some disentangle effects toward the environment. Hence, in this paper, the inhibition effect of neomycin trisulfate on the Klebsiella oxytoca on mild steel corrosion has been investigated using weight loss measurement, electrochemical impedance spectroscopy, Fourier-transform infrared, and scanning electron microscopy (SEM). These studies have shown that neomycin trisulfate shows better inhibition toward the microbe. The agreement with the experimental data was also found to be satisfactory. Further, surface morphological examination through SEM confirms that the inhibitor inhibits the microbes by blocking the EPS